Evaluation of Dichlorophenolindophenol (DCIP) test for Haemoglobin E (Hb E) in normal red cell indices individuals - Mohd. Yusoff, Mohd. Fauzi; Mohd Tohit, Eusni Rahayu; Hashim, Hafizah; Seman, Zainina (Universiti Putra Malaysia, 2021)
The current cut-off value for thalassaemia screening is based on a mean corpuscular haemoglobin (MCH) level of less than 27 pg. Samples with MCH < 27 pg require additional confirmatory testing, while samples with MCH > 27 pg are considered normal. However, there is a possibility of missing some types of haemoglobinopathy such as haemoglobin (Hb) E trait, by using this cut-off value. This study aimed to evaluate the dichloroindophenol (DCIP) test for Hb E carriers within healthy individuals. Methods: In total, 200 leftover blood samples with normal full blood count (FBC) results and MCH ≥ 27 pg were collected from students who were involved in the thalassaemia screening program. Blood samples were screened for Hb E by the DCIP test and subjected to haemoglobin analysis using capillary electrophoresis (CE) and gel electrophoresis. Results: Of the 200 leftover blood samples with normal FBC indices, 10 were positive for the DCIP test of which 8 had Hb E trait and 2 had Hb Constant Spring. The DCIP test showed 100% sensitivity and 98.96% specificity with a 100% negative predictive value (NPV) and an 80.0 % positive predictive value (PPV). Conclusion: The DCIP test was an excellent screening tool that, when combined with FBC parameters can produce better results, particularly in areas with a high Hb E incidence.